Phenotypic Characterization of Candida species in Tertiary Care Hospital of Eastern Nepal - Shrestha, Kewal; Yadav, Kumari Ragani; Singh, Ganesh Kumar; Bhattacharjee, Sujit Kumar (Journal of Nobel Medical College, 2022)
Background: Candida albicans is one of the most frequently isolated yeast in clinical laboratories and studies have shown that it accounts for up to 80% of the yeast recovered from the site of infection. Candida species have emerged as significant opportunistic fungal pathogens and the conventional methods of yeast identification are reported to be cumbersome with delayed diagnosis and initiation of treatment. Thus rapid identification and speciation of Candida species is essential in clinical laboratories. Materials and Methods: A hospital based cross sectional study was carried out in the department of microbiology, Nobel medical college from January 2020 to December 2020. Approval was acquired from the Institutional Review Committee. Various clinical specimens were obtained and identification as per the standard microbiological procedures. Data were analyzed by SPSS, version 20. Results: A total of 62 Candida species were isolated out of which 65% were from male and 35% were from female patients. Candida albicans was found to be the most common species with 68%. The highest incidence was seen in the age group below 20 years and 21 – 40 years with 32.25% cases each followed by 41-60 years with 20.96% cases. Among 62 specimens, urine samples yielded the highest number of Candida species 48.38% followed by sputum samples with 29.03% Candida species. High vaginal swab (HVS) yielded 12.9% Candida species and blood samples yielded 9.67% Candida species. Conclusion: Candida albicans is still the most significant clinically but other non albicans are also emerging significant pathogens and warrant routine discrimination in clinical laboratories.